2003
DOI: 10.1079/bjn2003993
|View full text |Cite
|
Sign up to set email alerts
|

Monounsaturated n-9 fatty acids and adipocyte lipolysis in rats

Abstract: To investigate the role of the monounsaturated n-9 fatty acids (MUFA) in the lipolytic activity of adipocytes, a study was carried out in which an increase in MUFA was produced in the tissues by two different methods; by the dietary enrichment of oleic acid or by producing an essential fatty acid deficiency syndrome. For this, forty-five male Sprague-Dawley rats were fed with a normal-energy diet and were subdivided into three groups. The diets varied in the type of dietary fat; palmitic acid, olive oil, or so… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
23
0

Year Published

2005
2005
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 41 publications
(26 citation statements)
references
References 45 publications
3
23
0
Order By: Relevance
“…There is increased sensitivity to catecholamine-induced lipolysis in visceral fat in non-obese individuals due to increase in the amount of β l and β 2 -receptors, with normal receptor affinity and normal lipolytic action of agonists acting at post-adrenoreceptor steps in the lipolytic cascade; this is associated with enhanced β 3 -adrenoreceptor sensitivity, which reflects changes in receptor number in comparison with subcutaneous adipocytes [29] .The site-related differences in lipolytic activity of fat cells may be due to differences in cyclic AMP production and β-adrenoceptor number, as catecholamines increase cyclic AMP production by stimulating β-adrenoceptors which leads to a sequence of events including elevation of adenylyl cyclase, activation of A-kinase and phosphorylation of hormone sensitive lipase HSL, ultimately resulting in an increase in lipolysis of fat cells as visceral fat cells contained a higher HSL activity than the subcutaneous cells [30]. Rat SC fat cells had lower HSL expressions compared to visceral fat cells [31].The of results of this study matched other studies that showed that diet can alter the ability of fat cells to transmit signals and that feeding SFAs results in lower activities in two major enzymes of the Lipolytic cascade: adenylate cyclase and HSL in SC, as SFAs decrease maximum lipolytic response to catecholamines in SC adipocytes with no change in ligand binding to B-receptor or in maximum basal adenylate cyclase activity [5,32,33].It was found that visceral adipocytes of animals fed SFAs release more glycerol than those of fed control diet due to increased B 3 -adrenoceptor function, and decreased α 2 -adrenoceptor function [34].The results of this study run parallel with several epidemiologic and clinical studies that describe an association between high-fat diets and worsening of insulin sensitivity and consequently its antilipolytic activity in fat cells. As some of the adipokines participate in the regulation of lipolysis in adipose tissue, especially TNF-α and IL-6 enhancing triglyceride hydrolysis, their plasma levels are positively associated with insulin resistance [35].…”
Section: Effect Of Diet Rich In Saturated Fat On Lipolytic Activity Osupporting
confidence: 79%
“…There is increased sensitivity to catecholamine-induced lipolysis in visceral fat in non-obese individuals due to increase in the amount of β l and β 2 -receptors, with normal receptor affinity and normal lipolytic action of agonists acting at post-adrenoreceptor steps in the lipolytic cascade; this is associated with enhanced β 3 -adrenoreceptor sensitivity, which reflects changes in receptor number in comparison with subcutaneous adipocytes [29] .The site-related differences in lipolytic activity of fat cells may be due to differences in cyclic AMP production and β-adrenoceptor number, as catecholamines increase cyclic AMP production by stimulating β-adrenoceptors which leads to a sequence of events including elevation of adenylyl cyclase, activation of A-kinase and phosphorylation of hormone sensitive lipase HSL, ultimately resulting in an increase in lipolysis of fat cells as visceral fat cells contained a higher HSL activity than the subcutaneous cells [30]. Rat SC fat cells had lower HSL expressions compared to visceral fat cells [31].The of results of this study matched other studies that showed that diet can alter the ability of fat cells to transmit signals and that feeding SFAs results in lower activities in two major enzymes of the Lipolytic cascade: adenylate cyclase and HSL in SC, as SFAs decrease maximum lipolytic response to catecholamines in SC adipocytes with no change in ligand binding to B-receptor or in maximum basal adenylate cyclase activity [5,32,33].It was found that visceral adipocytes of animals fed SFAs release more glycerol than those of fed control diet due to increased B 3 -adrenoceptor function, and decreased α 2 -adrenoceptor function [34].The results of this study run parallel with several epidemiologic and clinical studies that describe an association between high-fat diets and worsening of insulin sensitivity and consequently its antilipolytic activity in fat cells. As some of the adipokines participate in the regulation of lipolysis in adipose tissue, especially TNF-α and IL-6 enhancing triglyceride hydrolysis, their plasma levels are positively associated with insulin resistance [35].…”
Section: Effect Of Diet Rich In Saturated Fat On Lipolytic Activity Osupporting
confidence: 79%
“…39 Several studies have shown that circulating leptin concentrations were positively correlated with visceral adipose weight when comparing olive oil with high Fatty acid ratios on fat loss in diet-induced obese hamster F-H Liao et al saturated fatty acid palmitic acid, 40 and not influenced by high-fat rat diets containing different fat types compared with olive oil (MUFA), beef tallow (saturated fatty acid) or safflower oil (n-6 PUFA). 41 In contrast, despite similar food intake among groups, plasma leptin concentrations were also lower in HMHR groups, which is consistent with the lower epididymal white adipose tissue compared with the ObC group; however, no differences in plasma leptin concentrations and white adipose tissue were found between OO and ObC groups.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, significantly increased products of delta-9 desaturation and significant increases in C20 elongation products have been observed in rats with reduced food intake (33 ). On the other hand, smoking has been found to be associated with a decreased proportion of essential fatty acids (34 ), and essential fatty acid deficiency leads to a characteristic increase in -9 fatty acids (35 ). Because caloric restriction can lead to higher circulating concentrations of adiponectin in mice and humans (7 ), it is tempting to speculate that reduced food intake leads to increased adiponectin and C20:1 -9 concentrations concomitantly.…”
Section: Discussionmentioning
confidence: 99%